Non-Teaching Stakeholders’ Experiences with Inclusive Education in a Private School in Jamaica - Anderson Leachman, Kishi (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2023)
The literature is sparse on understanding the experiences of stakeholders with inclusive education in the Caribbean. Using a qualitative single case study, this study explores the lived experiences with inclusive education of non-teaching stakeholders (principal, dean of discipline, guidance counsellor, parents, and educational assistants) in a private school in Jamaica. Data was collected using individual interviews, focus group discussions and secondary data. Thematic analysis was used to interpret and present findings. Key findings revealed supportive school leadership, inconsistent teacher competence and pedagogy, controversies with educational assistants, and parental denial as barriers that undermine inclusivity. Leadership support that goes beyond the principal to include the school board of directors was highlighted as an important consideration. The study provides other implications and recommendations for the inclusive classroom in the Jamaican educational milieu. Although the findings are specific to this case, they can be transferred and applied to inclusive education in other contexts regionally and globally to inform inclusive practices and considerations.